Analytical quality by design approach to RP-HPLC method development and validation for simultaneous estimation of esomeprazole and naproxen in modified-release dosage form - Khandokar Farjana Urmi; Md. Saddam Nawaz; S. M. Ashraful Islam (SpringerOpen, 2022)
Abstract Background The present work describes the development and validation of a new, specific, accurate, and precise stability-indicating RP-HPLC method for the simultaneous estimation of Esomeprazole (ESP) and Naproxen (NAP) in modified-release bi-layer tablet dosage form. Analytical Quality by Design concept was implemented through the method development exercise to establish the robustness of the method. Results Method development was performed on C18, 250 × 4.6 mm ID, and 5 µm particle size column with 10 µl injection volume using a photodiode array (PDA) detector to monitor the detection at 280 nm. The mobile phase consisted of the buffer: methanol at a ratio of 50: 50 (v/v), and the flow rate was maintained at 1.5 ml/min, and the column oven temperature was maintained at 30 °C. The retention times for NAP and ESP were found 5.9 ± 0.1 and 8.9 ± 0.1 min, respectively. The method was validated in terms of system suitability, specificity, accuracy, linearity, precision, and solution stability. Linearity was observed over the range of concentration 8-12 µg/ml for ESP and 200-300 µg/ml for NAP, and the correlation coefficient (R 2) was found excellent > 0.999. The method was specific to ESP and NAP, and the peak purity was found 99.97% for ESP and 100.00% for NAP. The method was precise and had %RSD less than 2. Recovery study for accuracy with placebo was found in the range of 99.63-100.36% for ESP and 99.91-100.43% for NAP. Conclusion This proposed fast, reliable, cost-effective method can be used as a quality control tool for the simultaneous determination of Esomeprazole and Naproxen in routine laboratory analysis. Graphical Abstract